2010
DOI: 10.1016/j.vetmic.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of feline panleukopenia virus from a diarrheic monkey

Abstract: A feline panleukopenia virus (FPV) mutant, monkey/BJ-22/2008/CHN, was isolated from intestinal contents of a diarrheic monkey in Beijing, China. The virus was identified by morphology and physicochemical characteristics, and specific fragments were obtained by PCR using consensus primers of parvovirus and specific primers of FPV. Sequence of the full-length VP2 gene of the isolated FPV was determined and analyzed by comparison with reference FPV and canine parvovirus (CPV) isolates, showing high homology with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…These clinical samples had been used to investigate the prevalence of FBoV and FeAstV using conventional single PCR in a previous study CAT ACA TGG CAA ACA AAT AGA GCA 237 FPV-R TGT TTT AAA TGG CCC TTG TGT AGA FBoV NP1 FBoV-F AGA ACC RCC RAT CAC ART CCACT 465 FBoV-R TGG CRA CCG CYA GCA TTT CA FeAstV RdRp FeAstV-F GCG GAT TGG GCA TGG TTT AGA 645 FeAstV-R ACC CCT CGT TTG GAT CGT TACCT performed in our laboratory [24,25]. In the present study, these clinical samples were used to detect FPV using routine PCR as reported previously [23]. The positive rate was calculated for each virus, and the difference in the prevalence of each virus between diarrheic and healthy cats was evaluated by the two-tail chi square test using PASW Statistic 19.0.…”
Section: Application Of the Mpcr Assay On Clinical Samplesmentioning
confidence: 99%
“…These clinical samples had been used to investigate the prevalence of FBoV and FeAstV using conventional single PCR in a previous study CAT ACA TGG CAA ACA AAT AGA GCA 237 FPV-R TGT TTT AAA TGG CCC TTG TGT AGA FBoV NP1 FBoV-F AGA ACC RCC RAT CAC ART CCACT 465 FBoV-R TGG CRA CCG CYA GCA TTT CA FeAstV RdRp FeAstV-F GCG GAT TGG GCA TGG TTT AGA 645 FeAstV-R ACC CCT CGT TTG GAT CGT TACCT performed in our laboratory [24,25]. In the present study, these clinical samples were used to detect FPV using routine PCR as reported previously [23]. The positive rate was calculated for each virus, and the difference in the prevalence of each virus between diarrheic and healthy cats was evaluated by the two-tail chi square test using PASW Statistic 19.0.…”
Section: Application Of the Mpcr Assay On Clinical Samplesmentioning
confidence: 99%
“…Finally, the CPV-like phylogeny also contained individual sequences from a virus sampled from a masked palm civet (GenBank accession number EU441280) (X. Yan, H. Zhang, T. Chen, J. Zhao, X. Chai, and W. Wu, unpublished data), which was linked by a long branch to the intermediate raccoon group (although with weak support), and a virus associated with an outbreak in rhesus monkeys (GenBank accession FJ231389) (27) that falls at the base of the CPV-like part of the tree (again with weak support). Because these are single viral sequences, it is difficult to determine whether they simply represent transient spillover infections.…”
mentioning
confidence: 99%
“…The detection of kobuvirus was performed by RT-PCR using a pair of universal primer previously described (the primer sequences are shown in Table 1), UNIV-kobu-F/UNIV-kobu-R targeting 217-bp of partial 3D gene for all kobuviruses (Reuter et al 2009). These samples were also examined for other feline enteric viruses, including feline parvovirus (FPV) and feline bocavirus (FBoV), using PCR assays previously described (Takano et al 2016;Yang et al 2010). The amplified products were separated after electrophoresis on 1.5% agarose gels at 160 V for…”
Section: Detection Of Fekov and Other Feline Enteric Virusesmentioning
confidence: 99%